Between Genitive and Accusative Uses. On the Impact of Negation on Nominal Phrases Introduced by jako in Contemporary Polish - Gębka-Wolak, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The paper discusses research results based on data excerpted from the National Corpus of Polish. The analysis concerns the impact of negation on the grammar case used in nominal phrases introduced by jako. The purpose of our study was to establish the proportion of genitive and accusative uses in these contexts. We have also analysed the possible impact of the grammatical status of jako on the grammar case. We established that, in contemporary Polish, most nominal phrases introduced by jako contain genitive forms. Accusative forms, although rarer, may not be considered marginal, as they tend to appear in up to 34% of the contexts. We have also shown that there is a correlation between the grammatical status of jako and the way negation impacts these phrases. In structures where jako is considered part of the verb (e.g. Sportowiec nie traktuje trzeciego miejsca jako porażkę), accusative structures tend to appear more often than in those containing jako interpreted as independent lexical units (e.g. Nie znaliśmy tej dziewczyny jako studentki).